Status of Collection, Cultivation and Marketing of Medicinal and Aromatic Plants in Pithoragarh, Uttaranchal - Bisht, N. S.; Gera, Mohit; Sultan, Zafar; Gusain, M. S. (Indian Forester, 2005)
The status of collection, cultivation and marketing of medicinal and aromatic plants was studied in Pithoragarh District of UttaranchaI. The primary information was collected as per structured questionnaires from collectors/cultivators belonging to twelve villages spread over two blocks namely Munsiyari and Didihat. The important species being collected were observed to be Jhula, Reetha and Tejpat. The cultivators seem to be growing greater quantities of Atees, Gudhvach, Indrayan, Jambo, Jatamansi, Kalajeera, Kutki, Pashanbhed, Reetha, Same va and Tejpat. The most favoured market channel was observed to be Producer Middlemen Trader Consumer which was being adopted by 50% collectors and 90% cultivators. The producer’s share in consumer’s rupee in case of collection varied between 45.76.47% for different species with an average of 56.22%. Similarly the producer’s share in consumer’s rupee for cultivated species varied between 32.67- 89% with an average of 60.88%. The paper also discusses thc recent changes introduced by Uttaranchal Govt. in markcting of these medicinal and aromatic plant species.